Personal as public in Rohit’s Letters from Jail - Shrestha, Tara Lal (International Research Journal of MMC, 2026)
This study explores how Rohit’s Letters from Jail, addressed to his wife, illuminates a larger politico-cultural history of contestation and compromise. Employing Antonio Gramsci’s notions of ‘hegemony,’ and ‘resistance,’ Nancy Fraser’s ‘subaltern publics,’ and Carlo Ginzburg’s ‘microhistory,’ it investigates how his micro-level personal letters connect the macro-level politico-cultural contexts. It analyzes how his letters articulate an alternative public sphere depicting the hidden history of the community, whose contribution in nation building remained invisible in the elite public sphere, and locate the invisible-looking community as an insurgent intellectual. It attempts to substantiate how his letters depict his community, in Gramsci’s terms, as a ‘constructor,’ ‘organizer,’ and ‘permanent persuader.’ As subaltern studies members and microhistorians emphasize, his letters embody the story of resistance and resilience pertinent to rewriting the history from below movement. Readers realize how a small unit, an individual, or a community reflects a larger whole while reading his personal letters and reflecting the geo-political history. To support my argument, this study also uses insights collected between July 2025 to June 2026 when I participated Tamunjhya Literature Festivals in Bhaktapur, Thimi, Kathmandu and Kirtipur along with attending a dozen of social gatherings in which Rohit and his few supporters were present as literary and cultural critics rather than merely political activists. These literary and cultural public spheres articulated from the community offered a platform for collecting primary data through observations, reflections, interactions, and interviews supportive to this study. The finding and conclusion demand further inquiry to explore hidden history of Bhaktapur and its dynamics from microhistorical subaltern studies perspective.